Invertebrate post-segregation distorters: A new embryo-killing gene - Sinkins, S (2011)
Cytoplasmic incompatibility induced by inherited intracellular bacteria of arthropods, and Medea elements found in flour beetles, are both forms of postsegregation distortion involving the killing of embryos in order to increase the ratio of progeny that inherit them. The recently described peel-zeel element of Caenorhabditis elegans also uses this mechanism; like Medea the genes responsible are in the nuclear genome but it shares a paternal mode of action with the bacteria. The peel-1 gene has now been shown to encode a potent toxin that is delivered by sperm, and rescued by zygotic transcription of the linked zeel-1. The predominance of self-fertilization in C. elegans has produced an unusual distribution pattern for a selfish genetic element; further population and functional studies will shed light on its evolution. The element might also have potential for use in disease control. © 2011 Steven P. Sinkins.